Comparison of surgical and endovascular left subclavian artery revascularization during thoracic aortic endovascular repair: a systematic review and meta-analysis - Lin, Feng; He, Zhipeng; Gao, Junpeng; Huang, Xiaoci; Wang, Haoran; Han, Long; Zhu, Xingyang; Zhan, Yanqing; Wang, Wenbin (Frontiers in Cardiovascular Medicine, 2023)
Objective The purpose of this systematic review and meta-analysis was to incorporate data from the latest clinical studies and compare the safety and efficacy of surgical left subclavian artery (LSA) revascularization and endovascular LSA revascularization during thoracic endovascular aortic repair (TEVAR). Methods This study was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and was registered with the PROSPERO database on 16 April 2023 (CRD42023414579). The Embase, MEDLINE (PubMed), and the Cochrane Library databases were searched from January 2000 to May 2023. Results A total of 14 retrospective cohort studies with a total of 1,695 patients, were included for review. The peri-operative stroke rates of the surgical and endovascular LSA revascularization groups were 3.8% and 2.6%, respectively (P = 0.97). The peri-operative technical success rates for the surgical and endovascular LSA revascularization groups were 95.6% and 93.0%, respectively (P = 0.24). The peri-operative spinal cord ischemia rates were 1.6% (n = 18) and 1.9% (n = 7) in the surgical and endovascular LSA revascularization groups, respectively (P = 0.90). The peri-operative type Ⅰ endoleak rates for the surgical and endovascular LSA revascularization groups were 6.6% and 23.2%, respectively (P = 0.25). The subgroup analysis showed that the incidence of peri-operative type I endoleak in the parallel stent group was significantly higher than that in the surgical LSA revascularization group (P < 0.0001). The peri-operative left upper limb ischemia rates for the surgical and endovascular LSA revascularization groups were 1.2% and 0.6%, respectively (P = 0.96). The peri-operative mortality rates of the surgical and endovascular LSA revascularization groups were 2.0% and 2.0%, respectively (P = 0.88). Conclusion There was no significant difference in the terms of short-term outcomes when comparing the two revascularization techniques. The quality of evidence assessed by GRADE scale was low to very-low. Surgical and endovascular LSA revascularization during TEVAR were both safe and effective. Compared with surgical LSA revascularization techniques, parallel stent revascularization of LSA significantly increased the rate of type I endoleak.